Bimetallic NiSn supported on mesoporous carbon as an efficient catalyst for selective methanol synthesis from CO2 - Graciella Stephanie Dwiningtyas; Iman Abdullah; Ryohei Doi; Yuni Krisyuningsih Krisnandi (Carbon Resources Conversion, 2025)
Global warming and climate change represent the most significant environmental challenges of the 21st century, primarily attributed to the rise in CO2 emission in the atmosphere. Efforts to mitigate this increase involve exploring various methods to reduce CO2 levels, with chemical reactions, such as hydrogenation, being a prominent approach. However, the stable and inert nature of CO2 necessitates the use of catalysts to facilitate its conversion. In this research, NiSn nanoparticles with varying atomic ratios were deposited onto a mesoporous carbon support and subsequently utilized as catalysts for CO2 conversion through hydrogenation reactions at ambient pressure. The diffraction patterns of NiSn/MC reveal peaks indicating the presence of a graphitic carbon structure and the existence of a nickel-tin alloy. SEM-EDX mapping and TEM characterization demonstrate the uniform dispersion of NiSn particles on the mesoporous carbon surface, without the formation of agglomerated particles. Catalytic hydrogenation reactions indicate that the atomic ratio of Ni:Sn significantly influences the catalyst activity and selectivity for methanol formation. Among the NixSny/MC catalysts and monometallic Ni/MC, Sn/MC, and NiSn NPs without support, Ni5Sn1/MC demonstrated the highest CO2 conversion of 39.9 %. Additionally, at a reaction temperature of 175 °C and a CO2:H2 gas ratio of 1:7, Ni5Sn1/MC exhibited a methanol yield of 86.31 mmol/gcat, outperforming other catalysts in the study.